2014
DOI: 10.1364/oe.22.019850
|View full text |Cite
|
Sign up to set email alerts
|

Extreme events in chaotic lasers with modulated parameter

Abstract: We study a theoretical model describing a laser with a modulated parameter, concentrating on the appearance of extreme events, also called optical rogue pulses. It is shown that two conditions are required for the appearance of such events in this type of nonlinear system: the existence of generalized multi-stability and the collisions of chaotic attractors with unstable orbits in external crisis, expanding the attractor to visit new regions in phase space.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 24 publications
2
14
0
Order By: Relevance
“…This phenomenon can generate the spatiotemporal analog of chaos crisis, as theoretically demonstrated in a laser model in Refs. [77,78]. We have looked for this behavior in our data but we could not reliably extract the derivative of the Kaplan-Yorke dimension or of the maximum Lyapunov exponent with respect to the pump.…”
Section: Extreme Events Following Bifurcation To Spatiotemporal Cmentioning
confidence: 99%
“…This phenomenon can generate the spatiotemporal analog of chaos crisis, as theoretically demonstrated in a laser model in Refs. [77,78]. We have looked for this behavior in our data but we could not reliably extract the derivative of the Kaplan-Yorke dimension or of the maximum Lyapunov exponent with respect to the pump.…”
Section: Extreme Events Following Bifurcation To Spatiotemporal Cmentioning
confidence: 99%
“…Laser systems displaying extreme optical pulses, often referred to as optical rogue waves (RWs) [1], are being intensively investigated as they are excellent test beds to study extreme fluctuations under controlled conditions [2][3][4][5][6][7][8][9]. Rogue waves have been observed in many systems and were initially found in hydrodynamics, where occasionally, huge waves in ocean waters have been reported that, in contrast to tsunamis or solitons, can appear from nowhere, disappear in a short spatial length and do not necessarily propagate for long distances [10].…”
Section: Introductionmentioning
confidence: 99%
“…The method also gives information about patterns which are unlikely to occur before an extreme pulse, thus giving insight into "safe" time intervals. This approach could be valuable for studying the predictability of extreme optical pulses emitted by other laser systems [23][24][25]. Future work is aimed at testing this technique with optical experimental data and also, with data recorded from other systems that generate extreme fluctuations in their output signals.…”
Section: Discussionmentioning
confidence: 99%